Trauma-Informed Care in the UK: A Systematic Review and Thematic Synthesis of Qualitative Studies - Lotte Scheuner; Isabel Mark (BJPsych Open, 2025)
Aims: Experiences of trauma are highly prevalent within the UK. Within acute psychiatric care, current risk management includes the use of restrictive interventions. Frequent reports of re-traumatisation among service users have sparked debate about its effectiveness and acceptability. Trauma-informed care (TIC) has garnered more attention in recent years as a safer and more acceptable approach, aiming to recognise and respond to trauma in a way which resists re-traumatisation, but there is wide variation as to how this is implemented in the UK at present. The aim of this systematic review is to assess the effectiveness and acceptability of TIC in acute psychiatric care in the UK, and to determine its potential for national implementation.